2021
DOI: 10.1007/s00168-021-01073-y
|View full text |Cite
|
Sign up to set email alerts
|

Do population density, socio-economic ranking and Gini Index of cities influence infection rates from coronavirus? Israel as a case study

Abstract: A prominent characteristic of the COVID-19 pandemic is the marked geographic variation in COVID-19 prevalence. The objective of the current study is to assess the influence of population density and socio-economic measures (socio-economic ranking and the Gini Index) across cities on coronavirus infection rates. Israel provides an interesting case study based on the highly non-uniform distribution of urban populations, the existence of one of the most densely populated cities in the world and diversified popula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…There was a positive association between the Covid-19 risk and the population density. The importance of population density agrees with other studies (Arbel, Fialkoff, Kerner, & Kerner, 2021;Moosa & Khatatbeh, 2021;Sy, White, & Nichols, 2021;Wong & Li, 2020). Despite differences in localised structure, the RR values were similar for both G=2 and G=3 when population density was included (Table 4).…”
Section: Bayesian Spatial Car Localised Modelssupporting
confidence: 89%
“…There was a positive association between the Covid-19 risk and the population density. The importance of population density agrees with other studies (Arbel, Fialkoff, Kerner, & Kerner, 2021;Moosa & Khatatbeh, 2021;Sy, White, & Nichols, 2021;Wong & Li, 2020). Despite differences in localised structure, the RR values were similar for both G=2 and G=3 when population density was included (Table 4).…”
Section: Bayesian Spatial Car Localised Modelssupporting
confidence: 89%
“…The minimum is 5,232 persons (Geva Binyamin) and the maximum is 865,721 persons (Jerusalem). Indeed, Israel is characterized by high urbanization levels and non-uniform distribution of population densities, which, in turn, might increase the spread of the pandemic [ 8 , 9 ].…”
Section: Methodsmentioning
confidence: 99%
“…Referring to the COVID19 pandemic, Israel provides an interesting case study. Three salient features of Israel are: (1) an accelerated urbanization process and non-uniform distribution of population densities, which, in turn, might increase the spread of the pandemic [ 8 , 9 ], (2) disparities in household income and socio-economic ranking of municipalities (cities and towns) [ 27 ]; and (3) the early initiation of a nationwide vaccination campaign leading to the full vaccination (i.e., receipt of two vaccine doses) of more than half the population by the end of March 2021 [ 10 , 11 ]. There are currently three vaccine types in Israel: (1) Pfizer (approved on December, 2020), (2) Moderna (approved on August, 2021) and (3) Astra-Zenika (approved on September, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Spatial implications of the COVID-19 pandemic have been investigated from different perspectives. Some studies have analyzed geo-environmental factors (air pollution, weather conditions) (Coccia 2020 ), demographic characteristics (population density) (Mollato et al 2020 ; Arbel et al 2022 ), and climate conditions (temperature, humidity) (Oto-Peralías 2020 ; Ma et al 2020 ; Sajadi et al 2020 ; Wang et al 2020 ; Wu et al 2020 ; Rios and Gianmoena 2021 ) can affect the spread of COVID-19. Some studies have found a strong correlation between human mobility and the spread of disease (Chen et al 2020 ; Furceri et al 2020 ; Gross et al 2020 ; Zhang et al 2020 ; Hierro and Maza 2022 ).…”
Section: Spatial Implications Of Covid-19 Pandemic In Turkeymentioning
confidence: 99%